2020
DOI: 10.14336/ad.2019.0507
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Deficits Chronically Developed after Focal Ischemic Stroke and Beneficial Effects of Pharmacological Hypothermia in the Mouse

Abstract: Stroke is a leading cause of human death and disability, with around 30% of stroke patients develop neuropsychological/neuropsychiatric symptoms, such as post-stroke depression (PSD). Basic and translational research on post-stroke psychological disorders is limited. In a focal ischemic stroke mouse model with selective damage to the sensorimotor cortex, sensorimotor deficits develop soon after stroke and spontaneous recovery is observed in 2-4 weeks. We identified that mice subjected to a focal ischemic insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 66 publications
(91 reference statements)
0
13
1
Order By: Relevance
“…In light of this, there is now growing evidence demonstrating that NT(8-13) analogs induce regulated reduction of body and brain temperatures through activation of the NTS1 receptor subtype (Liu et al, 2016). Indeed, administration of the NTS1 agonists, NT69L, PD149163, HPI-201, or HPI-363, produced mild hypothermia and improved the neurological outcomes compared with that of results from external cooling (Katz et al, 2001;Choi et al, 2012;Wei et al, 2013;Lee et al, 2014Lee et al, , 2016Gu et al, 2015;Xue et al, 2017;Zhao et al, 2020;Zhong et al, 2020). Here, we therefore determined the ability of these specific pairs of NT(8-13) analogs to regulate the body temperature and evaluated the contribution of the receptor binding affinity and peptide plasma stability on the hypothermic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this, there is now growing evidence demonstrating that NT(8-13) analogs induce regulated reduction of body and brain temperatures through activation of the NTS1 receptor subtype (Liu et al, 2016). Indeed, administration of the NTS1 agonists, NT69L, PD149163, HPI-201, or HPI-363, produced mild hypothermia and improved the neurological outcomes compared with that of results from external cooling (Katz et al, 2001;Choi et al, 2012;Wei et al, 2013;Lee et al, 2014Lee et al, , 2016Gu et al, 2015;Xue et al, 2017;Zhao et al, 2020;Zhong et al, 2020). Here, we therefore determined the ability of these specific pairs of NT(8-13) analogs to regulate the body temperature and evaluated the contribution of the receptor binding affinity and peptide plasma stability on the hypothermic activity.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a series of studies has highlighted the benefit of achieving regulated reduction of body temperature using NTS1 agonists in different clinically relevant situations. For instance, systemic administration of NT69L, PD149163, or HPI-201 (formally ABS-201) produced mild hypothermia and exerted neuroprotective effects after ischemic stroke, intracerebral hemorrhage, resuscitation from cardiac arrest, and traumatic brain injury (Katz et al, 2001;Choi et al, 2012;Wei et al, 2013;Gu et al, 2015;Lee et al, 2016;Xue et al, 2017;Zhao et al, 2020;Zhong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…[18,114]. It should be pointed out that post-stroke depression/anxiety is also a common neuropsychological consequence of IS [115]. In addition, brain edema is the primary cause of IS mortality.…”
Section: Potential Dm-induced Mechanisms Leading To Diabetic Strokementioning
confidence: 99%
“…Acute ischemic stroke (AIS) is an increasingly prevalent threat to human health [ 1 , 2 ]. A recent epidemiological review concluded that stroke accounts for nearly 5% of all disability-adjusted life years and 10% of all deaths worldwide [ 3 , 4 ].…”
mentioning
confidence: 99%